Combining slightly acidic electrolyzed water and slurry ice to prolong the shelf‐life of mackerel (Pneumatophorus japonicus). Issue 9 (29th July 2021) - Liu, Lin; Lan, Weiqing; Pu, Tianting; Zhou, Yuxiao; Xie, Jing
Abstract: The comprehensive effects of slightly acidic electrolyzed water and slurry ice (SAEW‐SI) on the growth of microorganisms, physicochemical reaction, and sensory attributes of mackerel ( Pneumatophorus japonicus ) were evaluated during storage at 4°C. The changes in microbiological (total viable counts (TVCs), psychrophilic bacteria counts, pseudomonas bacteria counts, H2 S‐producing bacteria counts), physicochemical (pH, total volatile basic nitrogen (TVB‐N), water‐holding capacity (WHC), thiobarbituric acid reactive substances (TBARS), texture profile analysis (TPA), color difference, adenosine triphosphate (ATP)‐related compounds), protein characteristic (SDS‐PAGE, fluorescence spectroscopy analysis), and sensory evaluation were analyzed. It was observed that the SAEW‐SI treatment had a strong inhibitory effect on microbial growth (5.8 log CFU/g on 24th day). And SAEW‐SI could alleviate the oxidation degree of myoglobin and lipid, thus the color of samples was greatly maintained. According to the sensory attributes, the shelf‐life of samples in the SAEW‐SI group increased by 6 days compared to the control group. Therefore, SAEW‐SI could be a useful preservation approach for the fish industry. Novelty Impact Statement: The comprehensive effects of SAEW‐SI on the quality of mackerel ( Pneumatophorus japonicus ) were evaluated during storage at 4°C. SAEW‐SI showed the best antibacterial potential without any deleterious effects on the mackerel. SAEW‐SI could extend the shelf‐life of mackerel for another 6 days with a high sensory score.